CO2 storage in Residual Oil Zones: Field-scale modeling and assessment. (January 2017) - Jamali, Ali; Ettehadtavakkol, Amin
Highlights: Role of altered hydrodynamic flow field (AHFF) in ROZ formation is investigated. Tuned simulation model matched the characteristics of Permian San Andres ROZ. CO2 storage capacity under several EOR-storage strategies in ROZ are quantified. Effects of ROZ recoverable oil volume, biodegradation, and diagenesis are quantified. Opportunities and challenges of CO2 storage in ROZs are discussed. Abstract: Residual Oil Zones (ROZs) are formed as the result of secondary tectonic activities which trigger extensive oil remobilization after the primary petroleum migration. The ROZs are attractive targets for CO2 Enhanced Oil Recovery (CO2 -EOR) and storage: first, because in many cases, the thickness of the ROZ ensures an overall recoverable volume of oil comparable to that of the Main Pay Zone (MPZ) and second, because the ROZ has favorable containment and capacity for large-scale and long-term EOR-storage projects. This study investigates one of the underlying theories of the ROZ formation, called the Altered Hydrodynamic Flow Fields (AHFF). The impact of the AHFF process on the formation of ROZs is specifically investigated using a field-scale simulation model for a Permian Basin San Andres reservoir. The simulation model is tuned and verified by validating the ROZ's characteristics, such as the thickness of the ROZ, the shape of the saturation profile, and the tilt of the OWC. The tuned Permian Basin San Andres reservoir model is used to simulate the primary recovery and the secondary waterflooding phases in the MPZ. Depending on the CO2 availability and ROZ development strategy, six different development scenarios are specified beyond the waterflooding phase. The corresponding simulations are performed to find the optimum EOR-storage strategies for the MPZ-ROZ through the extensive comparison of key performance parameters, including the cumulative oil recovery, CO2 storage and, net CO2 utilization. The results confirm the technical viability of CO2 -EOR and storage in the ROZ. The most favorable expansion strategy in terms of oil production and CO2 storage is the simultaneous development of the MPZ and the ROZ from the beginning of EOR-storage process. Most importantly, the study demonstrates that the volume of the utilized CO2 has a substantial effect on the success of the EOR-storage. While other expansion strategies such as sequential development also provide reasonable oil production response and CO2 storage potential, early project expansion into the ROZ without sufficient investment in CO2 resources is shown to be detrimental to the economics of the project. Finally, several important technical considerations for CO2 storage are qualitatively discussed, including assessment of the ROZ storage capacity, saltwater disposal requirements, and reduced risk of CO2 leakage in the ROZ.